The effect of various steel fibers and volcanic pumice powder on fracture characteristics of Self-Compacting concrete. (20th December 2021) - Magbool, Hassan M.; Zeyad, Abdullah M.
Highlights: The aim of this paper is to investigate the effect of various steel fibers and volcanic pumice powder on fracture characteristics of self-compacting concrete. Volcanic pumice powder was used to replace 30% of the cement in self-compacting concrete. In addition, five different shape and aspect ratio fibers were examined, including the hook-end fiber with (60 and 30 mm), the long straight fiber with (21 and 13 mm), and the flat-end fiber for producing six different concrete mixtures by the addition of 1 percent by the volume fraction. The mechanical properties and fracture characteristics of concrete were evaluated. Abstract: The primary aim of this study is to examine the influence of incorporating volcanic pumice powder (VPP) and various steel fibers on the fracture toughness parameters of self-compacting concrete (SCC). Twenty-one notched SCCs with fiber (SCFs) beams and SCC beams (100 mm × 100 mm × 500 mm) are cast and then investigated via a three-point bending test. Five fiber types with different shapes and aspect ratios, namely, the hook-end fiber (60 and 30 mm), long straight fiber (21 and 13 mm), and flat-end fiber (six different concrete mixtures produced with the addition of 1% of the volume fraction), are examined. VPP is utilized at the replacement rate of 30% of cement mass. The other aim of the study is to examine the mechanical and fresh properties of concrete. Results show that steel fiber decreases the fresh properties of SCC. The inclusion of steel fiber leads to an increase in peak loads and deflection at the failure besides the mouth opening displacement of the crack. The parameters of fracture toughness of the concrete mixtures are also affected.